2014
DOI: 10.7249/rr559
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Research Strategy for Suicide Prevention in the Department of Defense: Status of Current Research, Prioritizing Areas of Need, and Recommendations for Moving Forward

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…A recent RAND study (Ramchand et al, 2014) suggested the majority of suicide prevention efforts in the DoD can be classified as primary prevention . As noted above, these programs tend to entail broad-based public awareness and education campaigns that focus largely on the communication of concerning symptoms and the availability of professional support services.…”
Section: Levels Of Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent RAND study (Ramchand et al, 2014) suggested the majority of suicide prevention efforts in the DoD can be classified as primary prevention . As noted above, these programs tend to entail broad-based public awareness and education campaigns that focus largely on the communication of concerning symptoms and the availability of professional support services.…”
Section: Levels Of Preventionmentioning
confidence: 99%
“…The abundance of primary and tertiary prevention approaches in the U.S. military contribute to speculative assumptions regarding how best to manage suicide and lessen its occurrence (Ganz et al, 2010;Ramchand et al, 2014). Clinical treatment methods (tertiary prevention) and resiliency training (primary prevention), for example, are more often seen as effective methods to reduce suicide risk among the general population (U.S. Department of Army, 2014).…”
Section: Suicide Prevention In Context Of Levelsmentioning
confidence: 99%
“…Recent reports of increased rates of suicide among active-duty military personnel (e.g., Ramchand, Acosta, et al, 2011) have garnered considerable attention and have spurred significant investments by DoD, the U.S. Department of Veterans Affairs (VA), and external organizations into research and prevention efforts (Ramchand, Eberhart, et al, 2014). Assessing service members' experiences with suicidal ideation and suicide behaviors is critical for informing resource allocation and identifying key targets for prevention programs.…”
Section: Suicidementioning
confidence: 99%
“…Historically, the U.S. military has had a lower suicide rate than the civilian population, and the suicide rate among U.S. military personnel has typically decreased during wartime (Cassimatis & Rothberg, 1997;Rothberg, Holloway, & Ursano, 1987). After 2000, however, the suicide rate among military personnel increased from 10.3 suicides per 100,000 service members in 2001 to 15.8 suicides per 100,000 in 2008 (Ramchand et al, 2014). This 50% increase across all the armed services was largely due to the doubling of the suicide rate in the U.S. Army, which is the focus of this paper.…”
Section: Increased Suicides In the Us Militarymentioning
confidence: 99%
“…Specifically, it provides a conceptual basis for synthesizing findings from studies conducted in both military and civilian samples. To our knowledge, none of the U.S. Department of Defense studies focused on suicide (totaling over US$165 million in funding to date; Ramchand et al, 2014) has examined aggregate level data as described here. The present review suggests that a number of relevant questions are not being asked in current studies.…”
Section: Implications For Suicide Researchmentioning
confidence: 99%